Use of phosphorus- and potassium-solubilizing multifunctional microbes to support maize growth and yield - Ana Khalisha; Rahayu Widyastuti; Iswandi Anas Chaniago (Sains Tanah: Journal of Soil Science and Agroclimatology, 2022)
Intensive chemical fertilizer use has led to environmental problems, ecological impacts, and dependence on chemical fertilizers. Microbial inoculants (biofertilizers) combined with mineral fertilizers can be used to establish an environmentally friendly and sustainable agricultural practice. This study aimed to observe the effectiveness of multifunctional microbes (S. pasteuri and A. costaricaensis) in their wild-type and mutant forms. The microbes can simultaneously solubilize phosphorus and potassium from minerals (rock P and feldspar) to support maize growth and yield. Microbial viability in the zeolite carrier was tested, and the treatment was applied to the field to determine the effect on maize growth and yield. The results showed that zeolite could maintain the microbe population at an average of 108 CFU g-1 during 4 months of storage. A field test revealed that all microbes treatments combined with minerals without the addition of chemical fertilizers could support maize growth and yield by producing maize ear. In particular, mutant A. costaricaensis can support dry stalk weight and maize ear length as effective as chemical fertilizers due to its ability to increase available P and exchangeable K in the soil. Overall, microbes could provide P but not K from the minerals and soil for plant uptake.